Strategic Planning in a Health Leadership Sector: A Report from UNESCO Chair in Health Education, Iran - K Bidad; F Farzadi; Z Pourpak; M Moin (Tehran University of Medical Sciences, 2009)
"nStrategic planning defines the formal decision of a company for its future. Like all organizations, health care sectors need to prepare their strategic planning and act according to it. UNESCO chair in health education as a leader health sector, describes the course and steps for preparing its strategic planning based on SWOT analysis technique.